A Study of Social Entrepreneurship in India -Opportunities and Challenges - Mr.E.Manikandan; Dr.C. Sengottuvel (Zien Journals, 2021)
Although social enterprises occupy themselves with the usual business aspects: an appealing product or service, good customer service, ensuring customers return; they can still be regarded as somewhat rebellious in the business milieu. As a social entrepreneur, your market is society and the product you are providing is innovation and transformation within this society. Though social enterprises have a lot in common with standard for-profit business models, maximizing financial returns is not the main aim. Here, the objective is social and environmental enhancement. Social entrepreneurship is, at its most basic level, doing business for a social cause. It might also be referred to as altruistic entrepreneurship. Social entrepreneurs combine commerce and social issues in a way that improves the lives of people connected to the cause. They don’t measure their success in terms of profit alone – success to social entrepreneurs means that they have improved the world, however they define that. Social entrepreneurs are individuals who try to tackle society’s most pressing problems and attempt to drive social innovation in fields such as healthcare, agriculture, education, environment and human rights, using new approaches and products and more rigorous applications of known technologies or strategies. The way they pursue these goals is what makes them distinctive. Similar to a business entrepreneur, a social entrepreneur operates with entrepreneurial determination and business methods to create financially-sustainable organisations that often have an income-generating stream built into the business model. A couple of keywords that are applicable to social entrepreneurs are: Innovation, Sustainability, Reach and Social Impact.
Keywords: Opportunity; challenges; entrepreneurs; commerce